2011
DOI: 10.1371/journal.pone.0017960
|View full text |Cite
|
Sign up to set email alerts
|

Mind Perception: Real but Not Artificial Faces Sustain Neural Activity beyond the N170/VPP

Abstract: Faces are visual objects that hold special significance as the icons of other minds. Previous researchers using event-related potentials (ERPs) have found that faces are uniquely associated with an increased N170/vertex positive potential (VPP) and a more sustained frontal positivity. Here, we examined the processing of faces as objects vs. faces as cues to minds by contrasting images of faces possessing minds (human faces), faces lacking minds (doll faces), and non-face objects (i.e., clocks). Although both d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
87
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 41 publications
5
87
2
Order By: Relevance
“…This pattern diverges from work suggesting that outgroup members are broadly dehumanized (Boccato, Capozza, Ralvo, & Durante, 2008). Faces with humanlike configurations may broadly activate social cognition early in the processing stream (Wheatley et al, 2011), which may account for the lack of differential dehumanization for the upright Black and White faces given the speeded nature of the task.…”
Section: Studymentioning
confidence: 99%
“…This pattern diverges from work suggesting that outgroup members are broadly dehumanized (Boccato, Capozza, Ralvo, & Durante, 2008). Faces with humanlike configurations may broadly activate social cognition early in the processing stream (Wheatley et al, 2011), which may account for the lack of differential dehumanization for the upright Black and White faces given the speeded nature of the task.…”
Section: Studymentioning
confidence: 99%
“…Indeed, humans are preferentially tuned to detect other faces (Ro, Russell & Lavie, 2001; Langton et al, 2008), and discriminate carefully between faces that are alive and those that are not (Looser & Wheatley, 2010; Looser, Guntupalli, & Wheatley, 2013; Wheatley et al, 2011). However, when the connection with other humans is deemed impossible, the drive to fulfill this motivation may manifest itself in the attribution of mental states to nonhuman entities, such as gadgets and pets (Epley et al, 2008).…”
mentioning
confidence: 99%
“…Lately, a lot of research has been devoted to how synthetic faces are perceived, but the results have been rather mixed. Some studies, for example those relying on functional magnetic resonance imaging (fMRI) and event-related brain potentials (ERP), found that artificial faces seem to be processed differently than real faces [15,16]. A similar conclusion was reached in a few studies exploring the recognition of emotions [17,18].…”
Section: Introductionmentioning
confidence: 68%